THE RELATIONSHIP OF ZOOM FATIGUE AND ACHIEVEMENT MOTIVATION IN NURSING STUDENTS - Yosep, Iyus; Sismayadi, Zahrul Insan; Mardhiyah, Ai; Maulana, Indra; Hazmi, Helmy (Journal of Nursing Culture and Technology, 2024)
Introduction: The impact of the Covid-19 Pandemic has disrupted various aspects, one of which is the education aspect which requires learning to be carried out remotely via video conference causing students to experience zoom tiredness. Besides that, as long as student study from the house via video conferencing, the potential happening decline in skills academic as a result competent students not achieved with good consequences from achievements motivation distracted students. Objective: The purpose of study he knew the connection Among Fatigue Zoom Levels with Achievement Motivation in student Faculty Nursing Universitas Padjadjaran in online learning during the Covid-19 Pandemic. Method: Population study student active S1 Faculty of Nursing Universitas Padjadjaran. Type study quantitative with design descriptive correlation. Sampling technique will use disproportionate stratified random sampling (n=271). The Instrument of study Zoom Exhaustion & Fatigue Scales for measure zoom tired and achievements motivation Scales for measure achievements motivation. Results: The results of data analysis were obtained sig. 0.000 < 0.05 with score correlation coefficient worth positive 0.289 which means strength relationship enough. Motivation owns a great influence on achieving learning. Although in implementation needed management good activity for avoiding possibility happening zoom tired. Conclusion: There is an adequate and positive relationship between zoom fatigue levels with achievement motivation in student Faculty of Nursing Universitas Padjadjaran during online learning in the pandemic period Covid-19.